In Vitro Neurotoxicity Resulting from Exposure of Cultured Neural Cells to Several Types of Nanoparticles. (8th March 2017) - Larner, Stephen F; Wang, Jonathan; Goodman, Jared; O'Donoghue Altman, Megan B; Xin, Meiguo; Wang, Kevin K W
Laboratory and industrial production of various nanoparticles, single-walled nanotubes (SWNTs), fullerene (C60), cadmium selenide (CdSe) quantum dots, carbon black (CB), and dye-doped silica nanospheres (NSs), has greatly increased in the past 15 years. However, little research has been done to analyze the toxicity of these materials. With recent studies showing that nano-substances can cross the blood–brain barrier, we examined the neurotoxicity of these manufactured nanoparticles. By employing the rat PC-12 neuronal-like cell line as the basis for our studies, we were able to evaluate the toxicity caused by these five nanoparticles. The level of toxicity was measured by testing for cell viability using the lactate dehydrogenase (LDH) cell viability assay, morphological analysis of changes in cellular structures, and Western blot analyses of αII-spectrin breakdown products (SBDP) as cell death indicators. Our results showed cytotoxicity in nondifferentiated PC-12 cells exposed to CB (10–100 µg/mL), SWNTs (10–100 µg/mL), C60 (100 µg/mL), CdSe (10 µg/mL), CB (500 µg/mL), and dye-doped silicon NSs (10 µg/mL). Exposure to higher concentrations (100 µg/mL) of SWNTs, CB, and C60 increased the formation of SBDP150/145, as well as cell membrane contraction and the formation of cytosolic vacuoles. The incorporations of the nanoparticles into cell cytoplasm were observed using the fluorescent dye-doped NSs in both nondifferentiated and nerve growth factor (NGF)-differentiated PC-12 cells. When PC-12 cells are differentiated, they appeared to be even more sensitive to cytotoxicity of nanoparticles such as CB 10 nm (10–100 µg/mL), CB 100 nm (10–100 µg/mL), and CdSe (1–10 µg/mL).